ISP-BASED MPLS VPN: OVERVIEW, TRAFFIC ENGINEERING SERVICES AND SOLUTIONS - Arshad, M. J.; Ahmad, H.; Samiullah, M.; Basit, A. (The Nucleus, 2014)
In recent years MPLS-Multiprotocol Label Switching enabled VPNs-Virtual Private Network have gained popularity as alternative to private WANs. MPLS-VPNs are more reliable, secure, scalable and cost effective than other candidate solutions. Traffic engineering (TE) is supported over MPLS, which allows network organizations to associate a LSP-Label Switched Path with the physical path they select. In this article, we present an implementation of traffic engineering over an Internet Service Prov ider (ISP)- based MPLS-VPN. We will start by defining the features, modes and preconditions for traffic engineering. Then we will explain what information needs to be disseminated to all the TE enabled routers and how the underlying routing protocol is modified to send it. Then we will define and configure MPLS TE tunnels. Finally, we will show how to achieve link protection in TE supported MPLS-VPN.